(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article discusses lighting as a language, addressing the perception, use, and occupation of space—all of which can be shaped and altered by light. The objective is to analyze the relationship between stage lighting and architectural lighting, investigating how these fields interact in the creation of space. A narrative literature review is conducted, drawing on works by theater authors in conjunction with contemporary architects. Drawing on the notions of visuality and visibility, the study highlights distinct concepts—such as illuminance, poetics, and living light—that go beyond the technical function of visibility and demonstrate light’s capacity to alter the perception of and the attribution of meaning to space.